Improving access to drug and alcohol treatment in NSW Australia: The role of self‐determination and peer support. (8th November 2021) - Bryant, Joanne; Horwitz, Robyn; Gray, Rebecca M.; Lafferty, Lise; Jops, Paula; Blunden, Hazel; Hudson, Suzie; Brener, Loren
Abstract: One of the key issues in the alcohol and other drug (AOD) treatment sector concerns the reported difficulties that clients have in accessing treatment. This paper draws on qualitative interview data collected from clients undergoing treatment ( n = 20) and stakeholders ( n = 15) of five specialist non‐government AOD treatment services in New South Wales, Australia, to offer an in‐depth perspective about treatment entry experiences. We identified four key themes of positive treatment entry experiences: the presence of high‐quality online information which enabled clients to best match themselves to treatment; flexible and simple intake procedures with skilled and welcoming staff; the presence and quality of social and other resources (such as families, peers and private health insurance) which enabled quicker access; and prior experience in the treatment system which helped clients to gain important knowledge and skills to improve future access. We discuss implications of these findings, including that waiting lists significantly exacerbate inequity, but that this could be ameliorated by providing peer‐support to those trying to gain entry, especially clients who do not have family and friends for help during this period. The findings also point to the way that client self‐determination is central to all positive treatment entry experiences, and that supporting clients to find 'the right fit' in relation to treatment options improves their experiences.